2023
DOI: 10.3390/plants12132441
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Nitrogen on the Yield Formation of Artemisia dubia Wall: Efficiency and Assessment of Energy Parameters

Abstract: With the increasing importance of energy crops, research on potential energy crops is carried out to identify plant species with high productivity and energy value. The field experiment with the new promising energy crop, Artemisia dubia (wormwood), was executed at the Vėžaičiai Branch of the LAMMC. The soil site was naturally acidic Retisol (pH 4.2–4.4). The species was investigated as an energy crop through the evaluation of its biomass productivity and some energetical qualities. According to the three inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…When evaluating the use of nitrogen fertilizers (N180), the calorific value of A. dubia was slightly lower. When evaluating the amount of nitrogen in the grown biomass, it was found that when nitrogen fertilizers were used, the amounts for Artemisia dubia biomass were higher than for the biomass grown in unfertilized soil [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When evaluating the use of nitrogen fertilizers (N180), the calorific value of A. dubia was slightly lower. When evaluating the amount of nitrogen in the grown biomass, it was found that when nitrogen fertilizers were used, the amounts for Artemisia dubia biomass were higher than for the biomass grown in unfertilized soil [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…These experiments were performed in the Thermal Equipment Research and Testing Laboratory of the Lithuanian Energy Institute (LEI). Based on standard methodologies, the lower and higher heating values (LHVs and HHVs) of the pellets, the values of chlorine and other elements, and the amount of ash after pellet burning were determined [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factor 2 was nitrogen rates. The seedlings were planted and fertilized by 3 nitrogen levels (0, 90 and 180 N kg ha -1 ) [24]. However, this article presented only two experiments, when nitrogen levels were 0 and the highest amount was 180 kg ha -1 .…”
Section: Methodsmentioning
confidence: 99%
“…In this respect, there are many sites that are not suitable for traditional agricultural crops here. Viewed from the other side, to not compete with traditional food crops, different alternative non-food crops or energy crops might be grown in the land which is less suitable or unprofitable for traditional farming land [24].…”
Section: Introductionmentioning
confidence: 99%